Association between maternal obesity and gestational diabetes mellitus and their related outcomes - Bharatnur, Sunanda; Acharya, Pooja B. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Gestational diabetes mellitus (GDM) has a direct correlation with maternal body mass index (BMI). Pre-pregnancy BMI is ideal for studying the outcomes of obesity in pregnancy. Unlike the west, in countries like India, pregnant women approach health facilities during first trimester making it appropriate to consider first trimester BMI, as a parameter to study outcome variables. In this study we correlate BMI and GDM in pregnancy as GDM has significant impact on mother and baby. Aim of study was to study maternal and neonatal outcomes in obese women who have conceived among two groups, GDM and non-GDM. Methods: Observational study conducted at tertiary care teaching hospital over a one-year period (2021-2022). All pregnant women in first trimester with Body Mass Index (BMI) ≥30, calculated in first visit, was included in this study for follow-up. According to the results of GDM screening at 24-28 weeks of gestation by DIPSI method, pregnancies were divided into the GDM and non-GDM group. They were observed for risk of GDM. The obstetric and neonatal outcomes were noted and compared between the two groups. Data was analysed using SPSS software. Results: Mean BMI (32.79±1.47) among GDM group is greater than Non GDM (31.15±1.22), with p-value 0.00005 is significant. In obstetric outcomes, GDM is associated with increased incidence of preterm deliveries (p-value=0.004), gestational hypertension (p-value=0.002). In case of perinatal outcomes, increase incidence of hyperbilirubinemia (p-value=0.002), hypoglycemia (p-value=0.048) and sepsis (p value=0.046) in neonates born to GDM is seen. Conclusions: BMI calculation in early pregnancy is good indicator to monitor for complications in pregnancy including GDM. Therefore, identification of patients with high BMI and GDM requires regular follow up during pregnancy so that early intervention minimises complications.